Combining Radiation Therapy with Immune Checkpoint Blockade for Central Nervous System Malignancies - D’Souza, Neil M.; Fang, Penny; Logan, Jennifer; Yang, Jinzhong; Jiang, Wen; Li, Jing (Frontiers in Oncology, 2016)
Malignancies of the central nervous system (CNS), particularly glioblastoma and brain metastases from a variety of disease sites, are difficult to treat despite advances in multimodality approaches consisting of surgery, chemotherapy and radiation therapy (RT). Recent successes of immunotherapeutic strategies including immune checkpoint blockade (ICB) via anti-PD-1 and anti-CTLA-4 antibodies against aggressive cancers such as melanoma, non-small cell lung cancer, and renal cell carcinoma have presented an exciting opportunity to translate these strategies for CNS malignancies. Moreover, via both localized cytotoxicity and systemic proinflammatory effects, the role of RT in enhancing anti-tumor immune response and therefore promoting tumor control is being re-examined, with several preclinical and clinical studies demonstrating potential synergistic effect of RT with ICB in the treatment of primary and metastatic CNS tumors. In this review, we highlight the preclinical evidence supporting the immunomodulatory effect of RT and discuss the rationales for its combination with ICB to promote anti-tumor immune response. We then outline current the clinical experience of combining RT with ICB in the treatment of multiple primary and metastatic brain tumors. Finally, we review advances in characterizing and modifying tumor radioimmunotherapy responses using biomarkers and microRNA (miRNA) that may potentially be used to guide clinical decision-making in the near future.